Housing Satisfaction of Psychiatric Patients in Different Forms of Housing—A Cross-Sectional Study in Berlin, Germany - Gutwinski, Stefan; Westerbarkey, Ella; Schouler-Ocak, Meryam; Moran, James K.; Schreiter, Stefanie (Frontiers in Psychiatry, 2021)
The growing social problem of homelessness and precarious housing situations has negative effects on psychological outcomes and quality of life (QoL) for mentally ill people. Despite a large body of research on QoL among homeless mentally ill people, research on housing satisfaction as a specific QoL domain and important outcome variable for treatment interventions is scarce. The purpose of this cross-sectional study is to investigate housing satisfaction among psychiatric patients in various housing situations. Out of 1251 patients that were treated in the targeted facilities during the admission period, 540 agreed to participate (43.2%). 123 participants were excluded from the analysis due to missing data, resulting in a sample of N = 417. Housing satisfaction data was assessed in a subjective screening and differences in satisfaction levels between housing status groups were analyzed. As hypothesized, more normative housing situations reported higher housing satisfaction. Homeless participants and those living in socio-therapeutic facilities were associated with more psychological and physical distress resulting from their housing situation than domiciled and flat-sharing participants. Problems of reducing homelessness and improving housing support are highlighted, as well as opportunities for improving support, particularly in therapeutic facilities.